Governance, regulation and innovation theory and evidence from firms and nations - edited by Mehmet Ugur. (Northampton Edward Elgar Pub, 2013)
This book aims to disentangle the complex relationship between innovation and its potential determinants, paying special attention to the roles of governance and regulatory frameworks, and the ways in which the latter interact with other drivers of innovation such as competition and the innovator's closeness to the technology frontier.
Includes index
Keywords: Governance